2004
DOI: 10.1143/jjap.43.4541
|View full text |Cite
|
Sign up to set email alerts
|

Shape Transition in the Initial Growth of Titanium Silicide Clusters on Si(111)

Abstract: The growth of titanium silicide clusters has been observed for sub-monolayer Ti deposited on Si(111)-7 Â 7. Irregular shape tetragonal Ti 5 Si 4 islands were observed to grow at 600 C. On the other hand, the elongated orthorhombic-Ti 5 Si 4 (O-Ti 5 Si 4 Þ clusters form at 700 C. The clusters underwent a rapid increase in length and slight reduction in width as the cluster area exceeds a critical size ($15 nm 2 Þ. The elongated clusters are oriented along three equivalent Sih2-20i directions of the Si(111) surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…4(b) and (e)). The faceted edges of the square silicide nanodots were parallel to the Si 110 direction, as observed by Chen et al 20 and Cheng et al 21 22 The square silicide nanodots were identified as epitaxial (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Upon annealing at 600 C, the morphology of silicide nanoparticles was close to spherical, as shown in Figures 4(c and f).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…4(b) and (e)). The faceted edges of the square silicide nanodots were parallel to the Si 110 direction, as observed by Chen et al 20 and Cheng et al 21 22 The square silicide nanodots were identified as epitaxial (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Upon annealing at 600 C, the morphology of silicide nanoparticles was close to spherical, as shown in Figures 4(c and f).…”
Section: Methodssupporting
confidence: 60%
“…3 In recent years, epitaxial silicide nanowires have been formed on Si substrate by self-assembled growth. [4][5][6][7][8][9][10][11][12][13] The epitaxial growth of silicide on Si substrate is a requisite property for the formation of nanowires. Thus, the only silicide nanowires with a specific phase and orientation can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, orthorhombic and tetragonal Ti 5 Si 4 may coexist at 700 C if the amount of deposited Ti is low. 22 It was previously found that the decrease in film thickness would result in the increase of the formation temperature of C49-TiSi 2 . 23…”
Section: Resultsmentioning
confidence: 98%
“…40 It is, however, interesting that TiSi 2 nanowires are incommensurate (8%) in their long direction. 46 However, the interface structure for the nanowires may not be the same as that inferred from the bulk lattices.…”
Section: Self-assembled Nanowiresmentioning
confidence: 98%